Evidence that the glucose transporter serves as a water channel in J774 macrophages. - Fischbarg, J (1989)
Water transport across plasma membranes is a universal property of cells, but the route of such transport is unclear. In this study, volume changes of cells of the J774 murine macrophage-like cell line were monitored by recording the intensity of light scattered by the cells. We investigated the effects of several inhibitors of glucose transport on cell membrane osmotic water permeability as calculated from the rates of cell volume change. Cytochalasin B (2.5 micrograms/ml), phloretin (20 microM), and tomatine (3 microM) reversibly blocked glucose uptake into these cells. All three inhibitors reversibly decreased the osmotic water permeability of J774 cells from 89.6 +/- 3.2 to 27.2 +/- 1.4 microns/sec. We conclude that a major component of the osmotic water flow across the plasma membranes of these cells is accounted for by water traversing their glucose transporters.